2021
DOI: 10.1111/dar.13271
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Queensland's Tackling Alcohol‐Fuelled Violence Policy on nightlife and business trade

Abstract: Introduction. Key elements of the Queensland Government's Tackling Alcohol Fuelled Violence (TAFV) policy included the introduction of mandatory identification (ID) scanners and reduced trading hours for licensed venues located within Safe Night Precincts (SNP). These measures raised concerns among licensed venue owners and other key stakeholders regarding the potential negative impact of the policy on business trade and nightlife. Using multiple data sources, this paper examines the impact of the TAFV policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The ability to receive an immediate alert when a banned person attempts to enter a venue clearly assists the enforcement of patron bans, but there is currently limited published research exploring the effectiveness of ID scanners. A recent study by de Andrade et al (2021) examined ID scanner data from 15 SNPs in Queensland. Of the scans undertaken during the period of the study, 0.21% detected an active banning notice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to receive an immediate alert when a banned person attempts to enter a venue clearly assists the enforcement of patron bans, but there is currently limited published research exploring the effectiveness of ID scanners. A recent study by de Andrade et al (2021) examined ID scanner data from 15 SNPs in Queensland. Of the scans undertaken during the period of the study, 0.21% detected an active banning notice.…”
Section: Discussionmentioning
confidence: 99%
“…Each scanner is networked through central servers and the details of any banned person are downloaded to all venues operating a scanner within around ten minutes of the ban being imposed. The QUANTEM project undertook an evaluation of the TAFV policy in 15 SNPs (Miller et al 2017(Miller et al , 2019, and findings have been reported within a range of papers (Carah et al 2021;Ferris et al 2021;Miller et al 2021b;Taylor et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The number of people entering licensed venues and moving through night-time precincts remained stable, and in some areas a greater diversification of entertainment offerings was observed. 40,41 This highlights the importance of documenting impacts beyond assaults and injuries, for example including impacts on nightlife and trade, in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Queensland Alcohol-related violence and Night-Time Economy (QUANTEM) project provides an example of how such a study could be conducted, using multiple data sources to measure impacts on alcohol-related health and social harms and local economies. [17][18][19][20][21][22][23][24] Furthermore, the ExILEnS study and research stemming from the NIHR School for Public Health Research alcohol programme demonstrate how impacts of local alcohol policies have been evaluated in UK contexts. 13 15 16 25 A well-theorised, robust impact evaluation of the LNL is overdue.…”
Section: Open Accessmentioning
confidence: 99%